Risk factors in preterm delivery of adolescent pregnant women in a hospital in Junín - Casimiro-Soriano, Enzo Martin (2023)
Objective. To determine the sociodemographic, obstetric, and pathological risk factors in preterm delivery of adolescent pregnant women in a hospital in the Junin region, Peru. Materials and Methods. Clinical records of 67 pregnant women and 134 controls between 10 and 19 years of age with a diagnosis of preterm delivery attended from January to December 2022 were reviewed. Bivariate and multiple logistic regression analysis was performed, as well as chi-square analysis with a significance of 0.05. Results. A positive, direct (OR>1) and significant (p<0.05) relationship was determined with the occurrence of preterm birth for the risk variables and multiple regression: Age 10-14 years (OR: 17.162; 95%CI: 1.665 - 176.925; reference "15-19 years"), housewife occupation (OR: 6.056; 95%CI: 2.699 - 13.587; reference "other occupations"), number of Pre-Natal Birth Controls (PNC) less than 6 (OR: 10.476; 95%CI: 4.279 - 25.648; reference "Equal or more than 6"), anemia (OR: 2.761; 95%CI: 1.080 - 7.060; reference "no"); urinary tract infection (OR: 2.754; 95%CI: 1.041 - 7.284; reference "no") and pre-eclampsia (OR: 5.751; 95%CI: 1.697 - 19.487; reference "no"). Conclusion. Early identification of risk factors and attention to pre-existing medical conditions in adolescents can help establish effective preventive measures and management strategies that improve delivery care and birth conditions for mothers and newborns.